UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV.A SD NEGERI 002 RAMBAH DENGAN MEDIA GAMBAR - Hapipah Hapipah (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to improve the results of learning mathematicsmaterial about the perimeter and area of the building flat andrectangle by using the image media on students SDN 002Rambah, Rokan Hulu. The subject of this research is thestudents of class IV.A. A which sample to 26 people. Actionresearch is carried out in 2 cycles. Data collection in thisstudy using test result and observation. Data of research resultanalyzed by descriptive quantitative. Result of researchindicate that learning by using image media of can improveresult of learning mathematics in perimeter and building areaflat in class IV.A SDN 002 Rambah. Initial condition of theresult before the action is given an average value of 60,15. Inthe first cycle by using the image media an increase so that theaverage value becomes 70,45. In cycle II show an increasewith the average obtained 85,60.